Development of digital competency curriculum framework for prospective ground handling professionals - Perdana Kusuma, Nur Makkie; Awan, Awan (Institute of Computer Science (IOCS), 2025)
The rise of IT technology in airports has highlighted the need for personnel equipped with digital skills to manage modern aviation operations effectively. This study investigates whether the current workforce possesses adequate IT competencies by conducting field observations at Yogyakarta International Airport (YIA) and interviews with its staff and general manager. The findings emphasize the pivotal role of IT skills in enhancing safety, streamlining operations, and delivering superior service quality. However, significant barriers, such as limited resources, resistance to change, and the absence of standardized frameworks, hinder the development of these competencies. The study proposes tailored training programs that integrate IT skill development into routine staff training and emphasizes the creation of a structured digital competency curriculum framework for ground-handling professionals. These results underscore the urgent need for digital competency development in the aviation sector, aligning with global trends that prioritize IT in improving reliability and safety standards. Addressing these gaps is imperative for fostering a resilient and adaptable workforce capable of meeting the industry's evolving technological demands